Reconciliation or Reconstruction? Further Thoughts on Political Forgiveness - Cahan, Jean Axelrad (Polity, 2013)
Over the past decade a substantial literature has emerged on the concept of political forgiveness and the process of restorative justice. This article argues that importing an idea of forgiveness into political affairs is a mistake. It is not necessary for the promotion of peace and security, and it is has been construed in a way that leans heavily toward Christian conceptions of forgiveness, as is evident in the influence of Desmond Tutu. The article also examines the influence of Hegelian recognition theory in current discussions of the political benefits of forgiveness, and reviews the cast of postwar German-Jewish relations, which conformed more closely to traditional Jewish thinking on forgiveness than to the Christian-Hegelian (multicultural) model.